Heartmate 3 implantation in small patients: CT-guided chest diameter assessment. (2nd February 2022) - Van Puyvelde, Joeri; Jacobs, Steven; Vlasselaers, Dirk; Meyns, Bart
Abstract: In recent years, the Heartmate 3 (HM3) has largely replaced the use of other intracorporeal left ventricular assist devices in the adult field. Because the HM3 is larger than the Heartware Ventricular Assist Device, the general consensus was that for small patients, the Heartware Ventricular Assist Device was the most appropriate implantable device option. Our goal was to describe our experiences with the successful implantation of the HM3 in 2 children, aged 9 and 11. We report on the chest cavity dimensions, as measured on computed tomography, that can be used to assess the feasibility of HM3 implantation in small patients. Abstract : The recent recall of the Heartware Ventricular Assist Device (Medtronic, Minneapolis, MN, USA) has created a challenge for left ventricular assist devices (LVADs) implantation in small patients [1].